MUC1 positive cutaneous metastasis with transepidermal elimination from a breast carcinoma - Luna, Amalia (2013)
Breast cancer is the most common cause of cutaneous metastases from internal malignancies. Generally, the neoplastic cells are located in the dermis or hypodermis, while a finding of transepidermal elimination on cutaneous metastases is exceptional. In this report we present a patient with perforating cutaneous metastases from breast cancer with mucin 1 expression. Cutaneous, bone, lung, and hepatic lesions were detected two years after the diagnosis of the primary tumor.